Pengaruh Disiplin Kerja, Motivasi, dan Kompensasi terhadap Kinerja Guru pada Sekolah Menengah Kejuruan di Kecamatan Sayung - Ahmad Nadial Kafi; Ibnu Khajar (Lembaga Yasin AlSys, 2025)
Teacher performance plays a strategic role in the success of vocational education; however, many vocational high schools still face challenges such as suboptimal work discipline, fluctuating work motivation, and compensation perceived as inadequate. This study aimed to analyze the effects of work discipline, work motivation, and compensation on the performance of vocational high school teachers in Sayung District. An explanatory quantitative approach was employed, using a saturated sampling technique that involved all 50 teachers as respondents. Data were collected through a questionnaire and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results show that work discipline has a positive and significant effect on teacher performance, while work motivation has a positive but not significant effect. Compensation was found to have a positive and significant effect on teacher performance, and jointly the three variables significantly influence performance with a coefficient of determination of 67.5%, indicating that work discipline, work motivation, and compensation explain most of the variance in teacher performance. In conclusion, work discipline and compensation are dominant factors in improving teacher performance, whereas work motivation needs to be strengthened through sustained managerial policies. The implications of this study highlight the importance of human resource management based on discipline, improved welfare, and effective school governance to reinforce the quality of vocational education at the vocational high school level.